Implementasi Nilai – Nilai Karakter Islami Dalam Pembelajaran Pai Di Era Digital - Arita Sanjaya (EL-EMIR Institute, 2026)
The rapid development of digital technology has significantly influenced the educational process, particularly in Islamic Religious Education (PAI) learning and the strengthening of students’ Islamic character. This study aims to analyze the implementation of Islamic character values in PAI learning in the digital era through the utilization of technology, classroom management strategies based on students’ learning styles, and the reinforcement of religious moderation in the educational process. The research employed a qualitative approach through library research and analysis of various scientific journals related to PAI learning, technology-based classroom management, and Islamic character strengthening. Data were collected through documentation, observation, interviews, and literature reviews from relevant academic sources. The findings indicate that the implementation of Islamic character values can be carried out through the integration of religious values, tolerance, discipline, responsibility, and noble morals (akhlaqul karimah) in digital-based PAI learning. The use of technology such as learning applications, educational videos, online platforms, and interactive media has improved the effectiveness of learning and assisted teachers in adjusting instructional strategies according to students’ learning styles. In addition, teachers’ role modeling, habituation of positive behavior, strengthening of Islamic digital literacy, and routine religious activities play an important role in shaping students’ moderate and noble character.